Form, Content, and Space: Methodological Challenges in the Study of Medieval and Early Modern European Graffiti - Mia Gaia Trentin (Papers from the Institute of Archaeology, 2021)
<!–[if gte mso 9]> Normal 0 false false false EN-GB X-NONE X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>Scholars of various disciplines have focused their attention on European Medieval and Early Modern graffiti during the last decade, thus confirming and reinforcing the value of this peculiar written evidence. Their contributions demonstrate that graffiti can offer valuable information to different fields of study (e.g. shipbuilding, palaeography, history, social culture, and visual culture) through a glimpse into past daily life. Due to their nature, graffiti present a completely free graphic expression, which may appear in either textual or pictorial forms, or both. This characteristic makes their study rather challenging due to the two different mechanisms of communication they employ. In the case of textual graffiti, the content is transmitted through linguistic codification, while pictorial graffiti require a decoding process that is more complex and articulated. The first challenge, though, is to find a way to record and compare both evidence on the same graphic and verbal levels. Furthermore, as for any other epigraphic evidence, the graffiti analysis must take into account the writing surfaces and the context, two elements that are fundamental for the final interpretation of this source. This paper will address these methodological issues concerning the preliminary phase of graffiti documentation and classification/cataloguing. The starting point has been the recent debate and application of FAIR data principles in the field of Humanities, which aim to create quality data, easily exchanged in a digital environment, fostering knowledge in the field. Since this approach has not yet been applied to graffiti studies, the paper aims to stimulate a dialogue on innovative and objective methodological approaches within the researchers’ community.
Keywords: Graffiti; Early Medieval; Europe